Adaptive multimodal surface patterning on a cylindrical shell panel using piezoelectric actuators. Issue 26 (26th October 2022) - Manoj Kumar, H.; Jose, Sandeep
Abstract: The present study demonstrates the feasibility of creating adaptive multimodal surface patterns on an otherwise featureless cylindrical shell surface with the help of surface-bonded piezoelectric actuators. These patterns can be tuned to transform into a periodic shape that spreads equally over the domain or can have the form of a localized dimple that is concentrated only over a portion of the domain of the structure. The possibility of controlling the number, location, and temporal order of these patterns by smart actuation is established. This tunability, in both topographic patterns and their feature locations, can offer dynamic and switchable functionalities for fruitful applications.